Efficacy of Polymate-777A in Reducing Formaldehyde Emissions from Plywood Panels to Improve Indoor Air Quality - S.C. Sahoo; Annesha Dutta; Chinmoy Das (Geography, Earth Science and Environment: Research Highlights Vol. 5, 2025)
Indoor air quality is significantly impacted by volatile organic compounds, with formaldehyde being a prominent concern due to its emission from wood composite products. Formaldehyde emissions from wood composite products are a big concern for the environment and people’s health. Formaldehyde is released from adhesives, coatings, and other products, leading to indoor air contamination and potential health risks, including respiratory issues and long-term exposure effects like cancer. This study investigates the efficacy of Polymate-777A, a formaldehyde scavenger, in reducing formaldehyde emissions from plywood panels. Through a series of controlled experiments, the impact of varying concentrations of Polymate-777A on formaldehyde release was evaluated using standardized testing methods to quantify emissions. The physical and chemical properties like colour, odour, solubility, pH, moisture content, solid content, and chemical compatibility with the resin were tested. The plywood properties, including glue shear strength in both dry and wet conditions, modulus of rupture (MOR), and modulus of elasticity (MOE), were evaluated according to IS 1734:1983 standards. Results indicate that the incorporation of Polymate-777A significantly reduces formaldehyde levels, enhancing the safety and environmental sustainability of plywood products. The results reveal that when 1.5% or more Polymate-777A was used as a scavenger for plywood manufacturing, the plywood met the emission standards set by Japan and Europe for formaldehyde emissions. This study suggests that using Polymate-777A could be a good way to reduce formaldehyde emissions from wood products, which would be better for the environment and people’s health. The researchers recommend further refining the concentration levels and incorporating Polymate-777A into manufacturing processes to meet even stricter emission standards.